2007
DOI: 10.1039/b702877f
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic diastereo- and positionselective oxidative mono-cyclization of 1,5,9-trienes and polyenes

Abstract: Ruthenium tetroxide (1 mol%) has been used as a catalyst for the oxidative mono-cyclization of 1,5,9-trienes and polyenes. The poly-unsaturated substrates underwent mono-cyclization with a high degree of diastereo- and positionselectivity to produce mono-tetrahydrofuran diols with a varying degree of unsaturation. Up to four new stereogenic centers were created in this single step transformation. The remarkable positionselectivity appears to be a result of relative electronic properties of the double bonds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…In fact, previous studies from our group had demonstrated that the oxidation of both linear and isoprenoid polyenes constantly furnishes poly-THF compounds possessing threo inter-THF relationships. This is consistent with the syn addition (a [3+2] cycloaddition) of a O=Ru-O portion across each involved C-C double bond, along the all- trans polyene chain ( Scheme 3 ), that also agrees with mechanistic proposals for related oxidative mono-cyclization of 1,5-dienes catalysed by RuO 4 [ 10 , 11 , 12 , 13 , 14 , 15 ] and related oxo-species OsO 4 [ 16 , 17 , 18 ] and MnO 4 - [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], as well as rhenium (VII)-mediated oxidative polycyclization of hydroxypolyenes [ 28 , 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 85%
“…In fact, previous studies from our group had demonstrated that the oxidation of both linear and isoprenoid polyenes constantly furnishes poly-THF compounds possessing threo inter-THF relationships. This is consistent with the syn addition (a [3+2] cycloaddition) of a O=Ru-O portion across each involved C-C double bond, along the all- trans polyene chain ( Scheme 3 ), that also agrees with mechanistic proposals for related oxidative mono-cyclization of 1,5-dienes catalysed by RuO 4 [ 10 , 11 , 12 , 13 , 14 , 15 ] and related oxo-species OsO 4 [ 16 , 17 , 18 ] and MnO 4 - [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], as well as rhenium (VII)-mediated oxidative polycyclization of hydroxypolyenes [ 28 , 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 85%
“…As a more recent contribution in this field Stark and co-workers investigated the mono-cyclization of a range of polyenes, namely 1,5,9-trienes, 1,5,9,12-tetraenes and squalene [102]. Selected examples are reported in Scheme 23.…”
Section: Ruthenium Tetroxide Chemistrymentioning
confidence: 99%
“…Oxidative monocyclization of polyenes. Overall yields including overoxidation products are shown in parentheses [102]. …”
Section: Ruthenium Tetroxide Chemistrymentioning
confidence: 99%
“…Bisepoxidation of the Δ 7 and Δ 15 double bond in the farnesyl residue (for atom numbering see Scheme 1), followed by regio- and stereoselective nucleophilic addition of water (and methylation) would deliver heronapyrroles A and B. Similarly, regio- and stereoselective nucleophilic addition of water to a tris -epoxy farnesyl intermediate 4 could initiate a cyclization cascade [1,3,8] that would provide the bis -tetrahydrofuran heronapyrrole C (Scheme 1), via a mechanism that closely resembles polyether antibiotic biosynthesis [1217]. This biosynthetic hypothesis raises the possibility that Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%